Pathophysiology and Diagnostic Evaluation of Occupational Asthma from Exposure to Wood Dust and Diisocyanates in the Wood Processing Employees: A Preliminary Study - Prasetyo, Eko; Anies, Anies; Widyastiti, Nyoman Suci; Suhartono, Suhartono (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study is a preliminary study to analyze the etiology and pathophysiology of exposure to wood dust and diisocyanates in the wood processing industry in Jepara, Central Java, Indonesia. This study also provides a diagnostic evaluation of occupational asthma (OA) for ongoing exposure. METHODS: The research method was carried out with a systematic review of various previous findings and with a preliminary study of workers in the processing industry in Jepara, Indonesia. RESULTS: The results show that from a sample of 32 respondents who have been carried out in a wood processing factory in Jepara, it shows that the suspect OA in sanding workers by hand is 75%, with the distribution of signs and symptoms: Chest tightness and pain (90%); cough (53%); shortness of breath (50%); and wheezing (2%). From the signs and symptoms felt, workers felt a continuous increase (progressivity) of OA by 75%. CONCLUSION: Theoretically, this preliminary study is useful to provide information about exposure to wood dust and diisocyanates as a risk factor for OA, especially among workers in the wood industry.